Negative association of serum neurofilament light chain with estimated glomerular filtration rate levels and the impact of gender - Peng, Hongyan; Liang, Zhuoxin; Huang, Bolun; Zhang, Senxiong; Yang, Yiyu (Frontiers in Neurology, 2024)
Background The relationship between kidney function and brain function is complex and poorly understood. This study aims to investigate the association between serum neurofilament light chain (sNfL) and levels of estimated glomerular filtration rate (eGFR), offering new insights into their interactions. Methods Data from the national health and nutrition examination survey (NHANES) in 2013–2014, linked with national death index records, were used. Participants who met specific criteria were analyzed. Baseline characteristics were stratified by tertiles of sNfL levels and compared using weighted Kruskal-Wallis and chi-square tests. Weighted linear regression models, both unadjusted and adjusted, evaluated the relationship between log sNfL and eGFR. Subgroup and interaction analyses validated the findings. Restricted cubic spline, scatter plots, and Spearman correlation confirmed the relationship between log sNfL and eGFR. Results A total of 2,038 eligible participants were included. Higher sNfL levels were significantly associated with lower eGFR (p < 0.01). The highest sNfL tertile had a significantly higher mortality rate (p < 0.01). Fully adjusted multivariable weighted linear regression showed a significant negative correlation between log sNfL and eGFR (per 10-unit increase; β = −0.07, 95% CI: −0.10 to −0.04, p < 0.01). Subgroup analyses consistently supported this negative correlation (p < 0.01). Interaction analysis revealed a significant gender difference (p = 0.032), with males showing a − 0.06 (−0.09, −0.04) decrease and females a − 0.07 (−0.11, −0.04) decrease in log sNfL per 10-unit increase in eGFR. Restricted cubic spline confirmed a linear relationship (p-non-linear = 0.121), and the Spearman correlation coefficient was −0.45. Females had slightly lower log sNfL levels compared to males at equivalent eGFR levels. Conclusion A significant negative correlation was found between log sNfL and eGFR levels. Gender influenced the degree of this negative association. Further research is needed to validate these findings and elucidate their underlying mechanisms.